Comparative Mitochondrial Genome Analysis of Mamestra configurata (Lepidoptera: Noctuoidea: Noctuidae) and Other Noctuid Insects Reveals Conserved Genome Organization and Phylogeny. (25th January 2022) - Zhao, Jing-Ru; Zhang, Si-Pei; Tang, Ying-Yu; Wang, Wei-Zhong; Tang, Bo-Ping; Liu, Qiu-Ning; Yang, Rui-Ping
Abstract: Mitochondrial genomes (mitogenomes) advance our understanding of molecular evolution and phylogenetic relationships. In this study, the mitogenome of Mamestra configurata was assembled, annotated, and analyzed. The total length of its genome was 15, 322 bp; the A+T content accounted for 81.2%. Both the AT and GC skew values (−0.003 and −0.182) in the mitogenome of M. configurata were negative. Compared with their ancestral insects ( trnI-trnQ-trnM ), the gene sequence showed a typical trnm rearrangement ( trnM-trnI-trnQ ). Except for cox1, all the protein-coding genes were initiated with ATN. All tRNAs except trnS1 were of the four-leaf grass type. According to phylogenetic analysis, we found that M. configurata and Protegira songi clustered together in one clade with high node support values. Based on Bayesian inference and maximum likelihood methods, the phylogenetic results revealed that M. configurata was closely related to Protegira songi, the Erebidae was sister to (Nolidae + [Euteliidae + Noctuidae]), Doidae and Notodontidae is sister to the other families of Noctuoidea, respectively. Our results may provide a useful reference for the intensive study of the phylogeny of Noctuidae.